A119: Deep Sequencing Analysis of the T Regulatory and T Effector Repertoire in Juvenile Idiopathic Arthritis. Issue 11 (March 2014) - Henderson, Lauren A.; Volpi, Stefano; Frugoni, Francesco; Kim, Susan; Janssen, Erin; Sundel, Robert P.; Dedeoglu, Fatma; Lo, Mindy S.; Hazen, Melissa M.; Mathieu, Ronald; Fuhlbrigge, Robert C.; Lee, Yu Nee; et al.
Abstract : Background/Purpose: T regulatory (Treg) function has been shown to be impaired in juvenile idiopathic arthritis (JIA) as synovial fluid (SF) Tregs are unable to suppress T effector cells (Teffs) found in the joint. The cause of this breach in immunologic tolerance is not fully understood, meriting the further study of Tregs and Teffs in JIA. The T cell receptor (TCR) endows T lymphocytes with antigen specificity and mediates interactions between T cells and their environment. Yet, little is known about the comparative specificities, clonality, and diversity of Tregs and Teffs in JIA. Further, the Treg repertoire has not been studied in adult or pediatric inflammatory arthritis. Therefore, we endeavored to characterize these TCR repertoires in JIA through deep sequencing technology. Methods: Mononuclear cells were isolated by Ficoll gradient centrifugation from paired peripheral blood (PB) and SF samples. Tregs (CD4 + CD25 + CD127 low ) and Teffs (CD4 + CD25 − ) were sorted by flow cytometry. The TCRβ chain was amplified by multiplex PCR with genomic DNA serving as the template and then deep sequenced (ImmunoSEQ™). Sequences were aligned to the reference International ImMunoGeneTics information system. Further analysis utilizing Immunoglobulin Analysis Tool software was done to assess clonality, diversity, and variable (V), diversity (D), and joining (J) usage. Statistical analysis was completed with paired/unpaired Wilcoxon signed‐rank and Kruskal‐Wallis tests. Results: Three girls and 2 boys with oligoarticular (n = 2), extended oligoarticular (n = 2), and psoriatic (n = 1) arthritis were studied. Patients were similar in age (7–12 yrs) and ANA status (negative n = 4). Treatment consisted of NSAIDs (n = 2), methotrexate (n = 1), leflunomide (n = 1), and leflunomide with etanercept (n = 1). Tregs, measured as % of CD4+ cells, were enriched in the SF compared to PB (mean ± SEM: SF Tregs 13.2 ± 1.8; PB Tregs 5.1 ± 0.6). SF Teff repertoire was less diverse (p = 0.008) and more clonal (p = 0.008) than PB Teffs. In SF Teffs, a single complementarity determining region 3 (CDR3) was shared across all patients, though different V and J genes were used to create this CDR3, suggesting antigen selection. SF Tregs had the largest clonal expansions compared to PB Tregs (p = 0.016), PB Teffs (p = 0.008) and SF Teffs (p = 0.032). The degree of SF Treg clonality correlated with the active joint count. V gene usage, particularly Vβ29, in unique clonotypes was skewed in SF Tregs compared to PB Teffs, PB Tregs, and SF Teffs (p = 0.022); Vβ29 gene overuse was most prominent in patients with more active joints. Conclusion: We report on the first deep sequencing analysis of T cells in JIA. An antigen‐driven process was suggested by the clonality and shared CDR3 clonotypes in SF Teffs. This study is the first to demonstrate abnormalities in the Treg repertoire in inflammatory arthritis. The SF Treg repertoire had the most pronounced clonality and skewing of V gene usage, and these abnormalities correlated with disease severity. These results suggest that Treg insufficiency in JIA may be partially due to an aberrant Treg repertoire in the arthritic joint. Studies of additional patients with functional correlates are needed to augment these findings.